EXPERT SYSTEM TO DIAGNOSE STUNTING DISEASE IN TODDLERS USING CERTAINTY FACTOR METHOD - Gea, Fide Evianti; Saragih, Rusmin; Ramadani, Suci (Journal of Mathematics and Technology (MATECH), 2024)
Stunting is a condition of failure to grow in children under five (infants under 5 years) as a result of chronic malnutrition is so necessary monitoring and assessment of nutritional status and growth of children according to the standards. Malnutrition occurs from infancy or in the womb in the early days after the baby is born, however, the condition of stunting only appears after the baby is 2 years old. According to the decree of the Minister of Health No. 1995/MENKES/SK/XII / 2010 on anthropometric standards for assessing the nutritional Status of children needs to be adjusted to the development and needs of community nutrition improvement programs. To overcome the problem of stunting status in children, it is necessary a system that can diagnose stunting disease based on symptoms felt in toddlers from an early age and can be done prevention and handling of child growth and development and can provide information to many parents at the time of counseling and guidance from health workers in posyandu activities. Based on the calculation of CF, the highest value is in stunting disease in toddlers with a value of 0.9428 or 94.28%. From the results obtained, the system identifies that the toddler is suffering from the type of anemia.